2015
DOI: 10.2166/wst.2015.360
|View full text |Cite
|
Sign up to set email alerts
|

Do wastewater treatment plants act as a potential point source of microplastics? Preliminary study in the coastal Gulf of Finland, Baltic Sea

Abstract: This study on the removal of microplastics during different wastewater treatment unit processes was carried out at Viikinmäki wastewater treatment plant (WWTP). The amount of microplastics in the influent was high, but it decreased significantly during the treatment process. The major part of the fibres were removed already in primary sedimentation whereas synthetic particles settled mostly in secondary sedimentation. Biological filtration further improved the removal. A proportion of the microplastic load als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
211
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 427 publications
(255 citation statements)
references
References 12 publications
18
211
0
2
Order By: Relevance
“…Generally, wastewater is highly contaminated with fibers with the average concentration being of 248 AE 109 fibers L À1 (mean AE SD, n ¼ 20) reaching a maximum of 473 fibers L À1 . In comparison, another study found similar values about 180 textile fibers L À1 [19]. Unlike fibers, fragments were only rarely collected, probably because of the low volumes of the samples (100-400 mL).…”
Section: Microplastics Encountered In the Different Compartmentsmentioning
confidence: 80%
“…Generally, wastewater is highly contaminated with fibers with the average concentration being of 248 AE 109 fibers L À1 (mean AE SD, n ¼ 20) reaching a maximum of 473 fibers L À1 . In comparison, another study found similar values about 180 textile fibers L À1 [19]. Unlike fibers, fragments were only rarely collected, probably because of the low volumes of the samples (100-400 mL).…”
Section: Microplastics Encountered In the Different Compartmentsmentioning
confidence: 80%
“…households, industrial activities, sometimes also storm water contains microlitter particles. Microlitter has also been detected in waste water effluents from Swedish and Norwegian STPs (Magnusson, 2014;Magnusson and Norén, 2014;Magnusson and Wahlberg, 2014;Talvitie et al, 2015). This shows that STPs are an entrance for microlitter to the aquatic environment (McCormick et al, 2014;Yonkos et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…However, there are some published papers on findings within the water column (e.g. Talvitie et al, 2015;Gewert et al, 2017) as well as ingestion in biota such as seabirds (van Franeker, 1985;van Franeker et al, 2011), fish (Skóra et al, 2012;Foekema et al, 2013;Bråte et al, 2016;Rummel et al, 2016) and invertertes (Vandermeersch et al, 2015;Wójcik-Fudalewska et al, 2016). The current data ground is small, but there are several ongoing projects on plastics in Nordic waters which have a specific focus on plastic ingestion.…”
Section: Contextmentioning
confidence: 99%